(3cJGH GdaJhIs
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdeJhGdi EMSGfg , GdbOje QVhGfg hHYO CjgG GdeDefhf Ef GdaJhI CUd bOje CRdi CHOi agi ai GdCUd GdEjeGf HGddg hUaGJ Gddg JYGdi s
(3BNQgG (B:s
(3hjbhd GdfbjH CjVkG Ef Mhd hLgg Yf gPG GdWQjb agh eJUa (B( (3HUaGJ (B) (3GdfaGb , hMGd GdefGabjf eYdhe HMVQJce ceG eQBfakG JeJ GdaJhI HGdJeGe hGdceGd ddTjN YHO GdbGOQ bOS Gddg QhMg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs